AB0104 Adrenal insufficiency primary antiphospholipid antibody syndrome and autoimmune hypothyroidism. (1st June 2001) - Foti, R; Incognito, C; Leonardi, R; Fagone, S; Bonincontro, L; Castellino, P
Abstract : Background: Adrenal Insufficiency (A. I.) is an uncommon complication of the antiphospholipid antibody syndrome (APS). Several cases of A. I. are described in association with APS in patients with Systemic lupus erythematosus (SLE) or other connective tissue disease; in contrast A. I. in association with Primary Anthipospholipid Syndrome (PAPS) is seldom described. Objectives: We report a case of adrenal failure as first manifestation of APS and autoimmune hypothyroidism. Our patient is a 65 years old female who a month before was admitted to her local hospital for fever, cough and dyspnea. She had no previous history of thromboembolic or connective tissue disease. Chest radiograph showed an infiltrate and pleural effusion, which cleared over the next two weeks and she was discharged. Within few days, she developed nausea, vomiting, mild abdominal pain and fever. On admission to our hospital, she was deydrated with pulse of 110/min, blood pressure 100/50 mmHg. Methods: Laboratory findings were: Hb 9.9 g/dl, WBC 16 × 10/ ³ μl, PLT 167 10 ³ μ/l, ESR 90 mm 1st h. Natremia was 128 mEq/l, kaliemia was 4.3 mmol/l. Gastroscopy was normal, a CT scan revealed a bilateral enlarged adrenal gland with a normal cava and iliac and femoral vein. Anorexia, vomiting, weakness, weight loss, orthostatic hypotension and hyponatremia led us to suspect an adrenal insufficiency diagnosis, that was confirmed by a low plasma cortisol concentration 3.5 mg/dl (n. 6–30) and by an ACTH test. The serum ACTH concentration was 900 pg/l (n.6–46), aldosterone < 5 pg/ml (n. 7.5–150). APTT was 83.8 sec.(n. 20–40sec) with normal PT. Lupus anticoaugulant was positive, Antiphospholipid antibodies IgG were positive:21.4 U/ml (n. <5). ANA, dsDNA and ENA were negative. TPHA, VDRL test, cryoglobulin and rheumatoid factor were negative. C3, C4 were normal. Antibodies against the adrenal cortex, tubercolin skin test and antibodies to HIV were negative. Thyroid hormones were: T3 0.56(n.0.45–1.37 ng/dl);T4 5.0 (n.4.50–12.00 ng/dl); FT3 1.90 (n.1.45–3.48 pg/ml); FT4 0.81 (n.0.71–1.85 ng/dl); TSH 7.44 (n.0.465–4.680 mUI/ml); TgAb 1:160; TMAb 1:160. Results: The diagnosis of AI secondary to PAPS associated with bilateral adrenal infarction, which was probably secondary to thrombosis of the adrenal glands veins, was made. In the course of hospitalisation the patient developed an extensive deep venous thrombosis of right iliac and femoral vein with estending up to the inferior vena cava. She was treated with hydrocortisone, fluorydrocortisone, heparin and L-thyroxine with rapid improvement in clinical and biochemical status. Conclusion: This case suggest that thrombosis of adrenal vein causing A. I. may be the first manifestation of PAPS and that the diagnosis of PAPS should be considered in patient with A. I; particular intriguing is the finding of autoimmune thyroid disease in a patient with A. I and PAPS.